IMPLEMANTASI METODE SIMULASI BERBASIS TEKNOLOGI INFORMASI DAN KOMUNIKASI DALAM MENUMBUHKAN KEAKTIFAN BELAJAR PESERTA DIDIK DI MADRASAH IBTIDAIYAH - Muzaini, M. Choirul; Najib, Muhammad; Mahmudah, Anis; Nisa, Ani Khoirotun (Prodi PGMI FTK UIN Ar-Raniry Banda Aceh, 2023)
The practice of learning carried out in school institutions with the implementation of a learning method is a common thing carried out by an educator in maximizing the desired learning objectives to be carried out. Various learning methods can be implemented for students in harmony with the characteristics of the students themselves. In this study the aim is to describe the Implementation of ICT-based Simulation Methods in fostering active learning of students in Madrasah Ibtidaiyah. This research uses a qualitative type of case study technique. Which was held at Madrasah Ibtidaiyah Darussalam Mataram Jaya. The data source uses primary data sources, namely grade IV (four) teachers and secondary data sources, namely in the form of documents and sources related to research. Research data collection techniques using the method of observation, interviews, documentation. In the technique of guaranteeing the validity of this research data using data triangulation. In the research, it was found that the simulation method can have implications for the active learning of students. Related matters can be known through each indicator of the activeness of students who are known to include: students participate actively in implementing assigned tasks by forming a group, actively asking questions, actively conducting group discussions, actively digging for information related to the discussion assigned to do the role-playing, and students participate actively in solving problems with the type of distributing the appropriate cast figures and can provide an assessment of the abilities they have.